2002
DOI: 10.1002/joc.740
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in the Colorado Rocky Mountains: free air versus surface temperature trends

Abstract: A high elevation data set of surface temperatures from the Front Range of the Rocky Mountains in Colorado, USA, is analysed for evidence of long-term change . Sites range from the high plains of Colorado (1509 m) to the alpine tundra (3749 m). Systematic changes in surface-based lapse rates are uncovered, with absolute cooling at the highest elevations, but little temperature change on the high plains. There is lapse-rate steepening at the higher elevations (>3000 m). A synoptic analysis using gridded pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 30 publications
11
132
2
Order By: Relevance
“…Mountainous environments are considered to be sensitive indicators of climate change (Liu and Chen 2000;Pepin and Losleben 2002;Nogués-Bravo et al 2007), leading to great interest in the climate change of mountainous regions. Recent concerns about regional climate change have focused attention on the dependence of climate variables on elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000;Marchenko 1999;Giese and Moβig 2004;Bolch 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mountainous environments are considered to be sensitive indicators of climate change (Liu and Chen 2000;Pepin and Losleben 2002;Nogués-Bravo et al 2007), leading to great interest in the climate change of mountainous regions. Recent concerns about regional climate change have focused attention on the dependence of climate variables on elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000;Marchenko 1999;Giese and Moβig 2004;Bolch 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is not a simple matter of adopting a fixed lapse rate, because near-surface air temperatures are determined by local surface energy balance (i.e., heat absorption in a forested versus glaciated environment) and by local air movements, such as cold air drainage patterns (see, e.g., Pepin & Losleben, 2002;Petersen & Pellicciotti, 2011;Shea & Moore, 2010). As discussed in Section 4, we observe a strong diurnal relation in the temperature difference between the Rogers Pass AWS and the glacier AWS and use this as the basis for temperature extrapolation to the glaciers.…”
Section: Albedomentioning
confidence: 99%
“…While several studies reported positive evidence (Beniston and Rebetez 1996;Diaz and Bradley 1997;Liu and Hou 1998;Liu and Chen 2000;Liu et al 2009), other studies found no evidence (Pepin and Seidel 2005;You et al 2008;You et al 2010) or even negative evidence (Vuille and Bradley 2000;Pepin and Losleben 2002;Lu et al 2010) of elevation dependency in surface warming based on the surface observations, though most climate models have found enhanced warming in the high-elevation regions (Giorgi et al 1997;Fyfe and Flato 1999;Snyder et al 2002;Chen et al 2003;Kotlarski et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Against the background of the global average surface temperature increase (especially since about 1950) (Solomon et al 2007), and the rapid retreat of mountain glaciers around the world (particularly in the Himalaya, Andes and Alps) (Solomon et al 2007), huge efforts have been made to explore the features and impacts of climate change in high-elevation regions Beniston 2003;Rangwala and Miller 2012). However, despite numerous studies in the past decades (Beniston and Rebetez 1996;Diaz and Bradley 1997;Liu and Hou 1998;Liu and Chen 2000;Vuille and Bradley 2000;Pepin and Losleben 2002;Vuille et al 2003;Pepin and Seidel 2005;Diaz and Eischeid 2007;Appenzeller et al 2008;Pepin and Lundquist 2008;You et al 2008You et al , 2010Liu et al 2009;Lu et al 2010), our understanding of whether elevationdependent warming commonly occurs in high-elevation regions, and whether high-elevation regions are warming faster than their low elevation counterparts, remains uncertain (Rangwala and Miller 2012).…”
Section: Introductionmentioning
confidence: 99%